ARTICLE REVIEW: EFFECTIVENESS OF COMBINATION OF PLANT EXTRACTS AS ALTERNATIVE HYPERTENSION THERAPY - Almasih, Royan; Hasimun, Patonah; Solihah, Nurlaella (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Hypertension is a global health problem requiring effective and safe management. Conventional therapies often face challenges, such as drug resistance, side effects, and patient non-compliance, increasing the need for alternative therapies. This article aims to review the effectiveness of plant extract combinations as antihypertensive therapies. This study used a literature review approach to studies published in the last 10 years, focusing on the mechanism of action, effectiveness, and synergistic potential of plant combinations. The results showed that combinations such as Anredera cordifolia (ten.) v. Steenis and Sonchus arvensis L. provided a decrease in systolic blood pressure (SBP) by 27.95 mmHg and diastolic blood pressure (DBP) by 33.89 mmHg, approaching the effectiveness of standard drugs such as valsartan. The main mechanisms include the inhibition of angiotensin-converting enzyme (ACE), vasodilation through the release of nitric oxide (NO), and diuretic effects. The combination of plant extracts shows potential as a safe and effective alternative; however, further clinical trials are needed to strengthen these findings. Keywords: Combination of Plant Extracts, Antihypertensive, Alternative Therapy.